Advanced Communication and Networking Third International Conference, ACN 2011, Brno, Czech Republic, August 15-17, 2011. Proceedings - Kim, Tai-hoon.; Adeli, Hojjat; Robles, Rosslin John.; Balitanas, Maricel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume constitutes the refereed proceedings of the 3rd International Conference on Advanced Communication and Networking, ACN 2011, held in Brno, Czech Republik, in June 2011. The 57 revised full papers presented in this volume were carefully reviewed and selected from numerous submissions. The papers focus on the various aspects of progress in Advanced Communication and Networking with computational sciences, mathematics and information technology and address all current issues of communication basic and infrastructure, networks basic and management, multimedia application, image, video, signal and information processing.
Keywords: Computer science; Computer Communication Networks; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Information Systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval; Management of Computing and Information Systems